The Impact Of The Covid-19 Pandemic On Economic Growth In Java Island - Ismiyanto; Rudatyo (IHSA Institute, 2022)
The global COVID-19 pandemic has altered the course of many facets of life, and Indonesia is no exception. Starting with the most severely impacted sectors (health, social, and economic), At both the global and national levels, the economic sector is in a slump. The economic impacts of the pandemic were especially severe in emerging economies where income losses caused by the pandemic revealed and worsened some preexisting economic fragilities. The island of Java, being the largest contributor to the rate of national economic growth, is thus inextricably linked to this issue. The purpose of this study is to determine the influence of the COVID-19 epidemic on economic growth in Java Island. This study employs a qualitative descriptive method, as well as a survey of relevant literature. According to the findings of this study, the province of Banten experienced the greatest contraction in economic growth on Java Island, with a rate of minus 3.38% in the fourth quarter, while the province of the Special Region of Yogyakarta experienced the greatest improvement, with a rate of minus 0.68% in the fourth quarter. To accelerate Indonesia's economic recovery, government policy efforts in revitalizing the processing industry, increasing access and capital for MSMEs, and optimizing the use of village funds in alternative development innovations during a pandemic with labor intensive development, BUMDes development, or development of tourism village potential must begin in Java.